2011
DOI: 10.1152/ajpgi.00453.2010
|View full text |Cite
|
Sign up to set email alerts
|

Sorting mouse jejunal epithelial cells with CD24 yields a population with characteristics of intestinal stem cells

Abstract: Intestinal stem cells (ISCs) have been studied for more than three decades; however, their isolation has remained a challenge. We hypothesized that, just as for stem cells of other tissues, one or more membrane markers would allow positive selection of ISCs by antibody-based sorting. To explore this hypothesis, microarray data of putative ISC fractions generated by side population sorting and laser capture microdissection were subjected to bioinformatic analysis to identify common membrane antigens. The microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
87
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 43 publications
6
87
0
Order By: Relevance
“…As a first step toward bringing ISC-focused therapies to clinic, several recent studies have utilized the groundwork laid by ISC biomarker discovery in mouse models to identify, isolate, and culture intestinal crypts and ISCs from human tissue (30,74,101). Human ISCs have been isolated from adult tissues using a combinatorial surface marker approach, based on previous observations in mice demonstrating enrichment for functional Lgr5ϩ ISCs in cell populations FACS-sorted for CD24 (31,99). Interestingly, in human intestinal epithelium, LGR5 is most significantly enriched in CD44ϩ/CD24Ϫ or CD44ϩ/CD24Ϫ/CD166ϩ populations, which also demonstrate functional stemness in basal culture conditions (30,101).…”
Section: Biomarkers and Signaling Network Bench To Bedsidementioning
confidence: 99%
“…As a first step toward bringing ISC-focused therapies to clinic, several recent studies have utilized the groundwork laid by ISC biomarker discovery in mouse models to identify, isolate, and culture intestinal crypts and ISCs from human tissue (30,74,101). Human ISCs have been isolated from adult tissues using a combinatorial surface marker approach, based on previous observations in mice demonstrating enrichment for functional Lgr5ϩ ISCs in cell populations FACS-sorted for CD24 (31,99). Interestingly, in human intestinal epithelium, LGR5 is most significantly enriched in CD44ϩ/CD24Ϫ or CD44ϩ/CD24Ϫ/CD166ϩ populations, which also demonstrate functional stemness in basal culture conditions (30,101).…”
Section: Biomarkers and Signaling Network Bench To Bedsidementioning
confidence: 99%
“…Flow cytometry of Paneth cells was performed using the method described by von Furstenberg et al (41). Briefly, jejunal epithelial cells were isolated using the EDTA-dispase method described by Formeister et al (12).…”
Section: Animalsmentioning
confidence: 99%
“…In vivo genetic lineage tracing studies in mice have demonstrated that the G protein-coupled receptor Lgr5, cell surface marker CD133, polycomb ring finger oncogene Bmi1, and telomerase (Tert) mark a population of IESCs in the crypt base of the small intestine. Additionally, the cell surface marker CD24 has been shown to be useful for fluorescent-activated cell sorting (FACS) enrichment of a small intestine IESC population that possesses stem cell characteristics, which are defined by multipotency and self-renewal capacity in vitro (15,44). Other studies in the small intestine have correlated gene expression patterns of Ascl2, Olfm4, Musashi1, and Dcamkl1 to IESC zone (17,22,30,42,43); however, it is still unclear whether these genes mark cells that possess functional stem cell properties based on in vivo lineage tracing or in vitro culture of FACS isolated cells.…”
mentioning
confidence: 99%
“…While considerable efforts have been made to define the genetic signature of small intestine epithelial cells (2,9,10,15,17,18,25,26,30,37,(41)(42)(43)(44), fewer studies have focused on identifying genetic biomarkers of colonic epithelial stem cells (CESCs) (11,13,36,39). The concept of two populations of CESCs has been postulated: one is a slowly dividing labelretaining population, and the other is an actively dividing high-turnover population (19).…”
mentioning
confidence: 99%